All Days 2012
DOI: 10.2118/161824-ms
|View full text |Cite
|
Sign up to set email alerts
|

Water Distribution in the Montney Tight Gas Play of the Western Canadian Sedimentary Basin: Significance for Resource Evaluation

Abstract: Water distribution in unconventional gas reservoirs is a key parameter that influences many aspects of resource exploitation including selecting geographic areas for multi-well development programs, identifying target zones for horizontal wells, calculating reserves, estimating permeability, and understanding variability in gas and water production. Insights on water distribution in the Montney tight gas play of northeast British Columbia and northwest Alberta were gained by integrating reliable bulk volume wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…A larger data set of permeability measurements (pressure-and pulse-decay) on the same formation collected from multiple wells was provided by Wood (2012) and is reproduced in Fig. 19.…”
Section: Discussionmentioning
confidence: 99%
“…A larger data set of permeability measurements (pressure-and pulse-decay) on the same formation collected from multiple wells was provided by Wood (2012) and is reproduced in Fig. 19.…”
Section: Discussionmentioning
confidence: 99%
“…The logging characteristics of the formation water residue in the gas reservoir are as that of the gas layer in the well logging curves, and there is no obvious water layer information. This water type is relatively common in lithologic gas reservoirs but rare in structural gas reservoirs (Wood, 2012). The logging response characteristics are low natural gamma, high resistivity and low water saturation, which are comprehensively judged as a gas layer by log interpretation.…”
Section: Formation Water Residue In the Gas Reservoirmentioning
confidence: 99%
“…The precipitation of salt in the rock samples is dependent on the Љin-situЉ water/brine content and the salinity of the Љin-situЉ (formation) water. Wood (2013) reported that while water saturations (bulk volume water) in Lower Montney are generally less than 1%, the water saturations in Upper Montney commonly rang between 1 and 3%. Wood (2013) further reported that, while there is no significant interrelationship between water saturation and porosity in Lower Montney, the water saturation in Upper Montney increases with increasing porosity.…”
Section: The Impact Of Salt Precipitation and Formation Water Salinitymentioning
confidence: 99%
“…Wood (2013) reported that while water saturations (bulk volume water) in Lower Montney are generally less than 1%, the water saturations in Upper Montney commonly rang between 1 and 3%. Wood (2013) further reported that, while there is no significant interrelationship between water saturation and porosity in Lower Montney, the water saturation in Upper Montney increases with increasing porosity. As highlighted by Wood (2013Wood ( , 2015, these data indicate that, compared to the Upper Montney, the Lower Montney is most likely at irreducible water saturation.…”
Section: The Impact Of Salt Precipitation and Formation Water Salinitymentioning
confidence: 99%
See 1 more Smart Citation